Influence of altitude and seasons on forage quality of Prosopis juliflora shrubs - El-Morsy M.H.M.; Assiri A.M.A.; Osman H.E.; Hashemi M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Fodder trees and shrubs in low rainfall areas are considered as an important source of feed adapted to harsh environments and overgrazing. A study was carried out to evaluate the quality indices of Prosopis juliflora forage shrub harvested in two growing seasons (spring and autumn 2013-2014) at three locations (Makkah, Jeddah, and Taif) in Kingdom of Saudi Arabia with varied altitudes. Forage harvested in spring had higher crude protein content but low crude fiber. The highest crude protein (CP) was found in forage growing in Taif (14.6%) characterized by high moisture availability and high altitude. In general, the values of ADF and NDF were relatively low and ranged from 26-42%. Forage harvested from Taif, had less NDF and ADF than that harvested from the other two locations. Nitrogen free extract (NFE) which represents the amount of carbohydrates in forage was higher in spring than in autumn. Calcium (Ca), phosphorus (P), potassium (K) and magnesium (Mg), total digestible nutrients (TDN), digestible energy (DE), metabolized energy (ME) and net energy (NE) were not affected by seasons or sites or their interaction?
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)